The Impact of Chemical Treatment of Cellulosic Fibers on Surface Properties and Matrix/reinforcement Interfacial Adhesion. Issue 15 (23rd November 2022) - Elaissi, Arwa; Alibi, Hamza; Ghith, Adel; Legrand, Xavier
ABSTRACT: This paper aims to assess the potential for the use of waste cellulosic fibers and recycled grains as materials for the development of abrasives. However, abrasive wear produces low durability and a lot of waste. The improvement of adhesion between the components of composites is the key to extending their lifetime. For this purpose, the surface of the fiber was modified by cationic reactive agents. Composites were manufactured with treated fibers, polyurethane matrix, and iron shavings as abrasive grains. To obtain this product, the coating phenomenon is maintained. DSC and TGA analysis show the thermal stability of abrasives. Contact angle and zeta potential measurements have been used to evaluate the specific surface-chemical changes imparted by surface treatments of specimens. EDX and SEM observations indicate that matrix-reinforcing particle-phase boundaries have a very important effect on the using properties of these materials and revealed that the abrasion resistance of composite is sensitive to fiber/matrix adhesion.